2003
DOI: 10.1002/ejoc.200300387
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Solution‐Phase Parallel Synthesis of 4‐Substituted N‐Protected Piperidines

Abstract: Practical conditions for the synthesis of 4‐substituted N‐protected piperidines through CuCN·2LiBr‐catalyzed organozinc additions to 1‐acylpyridinium salts and subsequent hydrogen‐transfer hydrogenation have been established. The reaction sequence is performed at room temperature and provides 4‐substituted N‐protected piperidines in excellent overall yields without the isolation of intermediate dihydropyridines. In those cases in which the organozinc addition results in mixtures of 2‐ and 4‐substituted dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In a collaborative effort, our laboratories recently started to look at the potential of using pyridine N-oxides as starting material for the synthesis of 2-substituted piperidines. 6 We confirmed previous results reported on dienal-oxime formation, and in addition found that a fast addition rate of the Grignard reagent to the pyridine Noxide dissolved in THF was important for achieving high yields of the dienal-oximes. 7 Further studies showed that the reaction was compatible with a variety of differently substituted pyridine N-oxides and Grignard reagents (Scheme 1).…”
Section: Fredrik Almqvistsupporting
confidence: 91%
See 2 more Smart Citations
“…In a collaborative effort, our laboratories recently started to look at the potential of using pyridine N-oxides as starting material for the synthesis of 2-substituted piperidines. 6 We confirmed previous results reported on dienal-oxime formation, and in addition found that a fast addition rate of the Grignard reagent to the pyridine Noxide dissolved in THF was important for achieving high yields of the dienal-oximes. 7 Further studies showed that the reaction was compatible with a variety of differently substituted pyridine N-oxides and Grignard reagents (Scheme 1).…”
Section: Fredrik Almqvistsupporting
confidence: 91%
“…When 4-substituted products are desired, a practical solution is to remove the undesired conjugated 2-regioisomer by trapping it via a Diels-Alder reaction. 6 (1) Nevertheless, the strategy of using activated pyridines is attractive, and additional methods using activated pyridine derivatives with directing groups have been reported. In 2001 Charette and co-workers presented a method for the synthesis of substituted pyridines and piperidines.…”
Section: Synthesis Of Pyridinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since α‐ketols 12 were obtained in 4–9 % yields in the Reissert‐type acylation of quinolines by Cu I /CH 2 Cl 2 catalytic systems, the acyl Cu species might be involved in these preferred 1,4‐addition reactions. Such a preferential formation of 1,4 adducts has been reported in Reissert‐type transformations of quinolines and pyridines by using organocopper compounds8a8c or organometallic compounds with Cu I additives 5e,6d,8d,8e. Although details about the solvent effect22 and the role of the cationic Rh I catalyst23 for the regioselectivity remain uncertain at present, the cationic Rh I catalyst might take part in promoting the generation of N ‐acylquinolinium intermediates 13 24…”
Section: Resultsmentioning
confidence: 88%
“…3-Alkylpyridines also form the corresponding pyridinium salts, however deprotonation is not possible with mild base because the resulting 3-pyridylic anion would not be resonance-stabilized by the pyridine nitrogen. The heterobenzylic position in 2-alkylpyridines is inherently activated by the ring, and these substrates also form the required pyridinium salts readily, 19 however they cannot be deprotonated with mild base. The reasons for this are unclear at present but may reflect an orthogonal relationship between the heterocycle and the alkoxycarbonyl group in the pyridinium salt or developing allylic strain during the necessary deprotonation step.…”
Section: Reaction Design and Developmentmentioning
confidence: 99%